Strong upconversion-downshifting green emission from Tb3+ ions in core/shell/shell-structured nanophosphors - Juarez, Xitlali G.; Ko, Hyungduk; Jang, Ho Seong (SPRINGER, 2018)
Efficient upconversion (UC)-downshifting (DS), dual-mode-emitting NaGdF4:Yb,Tm/NaGdF4:Tb/NaYF4 core/shell/shell (C/S/S) nanophosphors (NPs) were synthesized. The UC luminescence color changed from blue to sky blue after doping Tb3+ into NaGdF4 shell because Tb3+ emission peaks via D-5(4) -> F-7(J) transition were observed with Tm3+ emission peaks via D-1(2) -> F-3(4) and (1)G(4) -> H-3(6) transitions through the energy migration UC process of Yb3+ -> Tm3+ -> Gd3+ -> Tb3+. Upon increasing the Tb3+ concentration in the NaGdF4 shell from 5 to 15%, the Commission Internationale de l'Aeclairage (CIE) color coordinates changed from (0.2188, 0.2390) to (0.2616, 0.3654). When NaGdF4:Yb(49%),Tm(1%)/NaGdF4:Tb(15%)/NaYF4 NPs were excited using 273 nm ultraviolet light, the C/S/S NPs exhibited bright green light with CIE color coordinates of (0.3354, 0.5090) as a result of energy transfer from Gd3+ to Tb3+. These bright UC-DS, dual-mode-emitting C/S/S NPs could be applied in various applications, including multiplexed imaging and anticounterfeiting.
Keywords: ENERGY MIGRATION; SHELL NANOPARTICLES; POLYMER COMPOSITES; NAYF4 NANOCRYSTALS